2018
DOI: 10.3892/mmr.2018.9389
|View full text |Cite
|
Sign up to set email alerts
|

Effects of leptin on neurocognitive and motor functions in juvenile rats in a preterm brain damage model

Abstract: Preterm infants face lifelong disabilities, including learning disorders, as well as visual, auditory and behavioral problems. Recent studies have demonstrated that leptin, an adipocytokine encoded by a gene associated with obesity and expressed in adipose tissue, affects neurocognitive and motor function; however, the mechanisms of brain damage in preterm infants are unclear. In the present study, the neuroprotective effects of leptin in a rat model of preterm hypoxic‑ischemic brain damage were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 43 publications
(77 reference statements)
1
1
0
Order By: Relevance
“…So, it is of great clinical significance to select PD28 rats for neurobehavioral assessment. Morris water maze is a classic experiment to evaluate hippocampal function [30]. The present study showed that HI insult induced significant long-lasting cognitive deficits in rats.…”
Section: Discussionsupporting
confidence: 54%
“…So, it is of great clinical significance to select PD28 rats for neurobehavioral assessment. Morris water maze is a classic experiment to evaluate hippocampal function [30]. The present study showed that HI insult induced significant long-lasting cognitive deficits in rats.…”
Section: Discussionsupporting
confidence: 54%
“…Sahin et al (2020) reported that leptin induces synaptogenesis in the developing hippocampus through increased expression of KLF4 and cytokine signaling suppressor 3 (SOCS3) in hippocampal neurons [ 97 ]. Additionally, it exhibits neuroprotective effects and alleviates spatial memory impairment in rat studies of premature brain injury, which may contribute to a better understanding of the protective effect of this hormone in premature infants with cerebral hypoxia [ 98 , 99 ].…”
Section: The Importance Of Vitamins and Hormonesmentioning
confidence: 99%